Pengaruh Pengetahuan Keuangan Dan Kepribadian Terhadap Keputusan Investasi Melalui Perilaku Keuangan Pada UMKM Kota Padang - Ubadinul Khairat; Lusiana Lusiana; Putri Azizi (Universitas 45 Surabaya, 2024)
This research aims to test how much influence financial knowledge and personality have on investment decisions through financial behavior in Padang city MSMEs. The data collection method is through surveys and distributing questionnaires, with a sample of 100 respondents. The analytical method used is structural equation modeling using smartpls. The research results showed that there was a significant influence of financial knowledge on financial behavior. There is a significant influence of personality on financial behavior. There is a significant influence of financial knowledge on investment decisions. There is a significant influence of personality on investment decisions. There is a significant influence of financial behavior on investment decisions. Financial behavior mediates the influence of financial knowledge on investment decisions. Financial behavior mediates the influence of personality on investment decisions.